SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL STUDY OF VANGA BHASMA PREPARED WITH SPECIAL REFERENCE TO RASATARANGINI (International Journal of Ayurveda and Pharma Research, 2021)
Vanga Bhasma which has been prepared with Parada and Haratala or even without Parada and Haratala is widely used for a broad spectrum of diseases. It is also said to possess Jantughna Prabhava (Antimicrobial activity). Hence it was decided to synthesize, analyse and study the antimicrobial activity of Vanga Bhasma prepared with special reference to Rasatarangini 18/25-28. The present study deals with the preparation of Vanga Bhasma with reference to Rasatarangini 18/25-28. The synthesized Bhasma samples were characterized by various analytical techniques. The antimicrobial effects of these Bhasma samples were studied. The samples were characterized with the contemporary parameters like XRD, SEM and EDX to find out the nature of the Vanga Bhasma samples. These samples were further tested against certain Gram +ve, Gram-ve and fungal organisms, so as to find out the anti-microbial efficacy of the Vanga Bhasma samples. The adopted method for preparation of Vanga Bhasma (Ref. Rasatarangini 18/25-28) was able to produce a Bhasma compatible to organoleptic parameters mentioned in the ancient texts. Formation of the small sized particles as small as a nano-particle was confirmed by SEM study. Average 14 Putas are required to prepare Vanga Bhasma and XRD study confirms that Tin oxide is the major compound. Vanga Bhasma showed antimicrobial activity in inhibiting the growth of Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumonia, Escherichia coli and Candida albicans with a concentration of 100mg/ml. This outcome further supports the Krumighna and Jantughna properties (anti-microbial activity) of Vanga Bhasma.